ISOLATION, CHARACTERIZATION AND ANTIOXIDANT ACTIVITY STUDY OF CATECHINS FROM WHITE TEA (CAMELLIA SINENSIS) - Budi Utami, Praptaning
Tea is one of the most consumed plantation products in Indonesia and the world. The tea leaves come made from Camellia sinensis plant. Besides its popular taste, several compounds in tea have been scientifically proven to have antioxidant activity which is can be used in the medical, cosmetics, industrial, and others. This research has a procedure consisting of isolation, characterization, and computational analysis studies of the antioxidant capacity of caffeine and catechins. Liquid-liquid extraction was carried out to isolate crude catechin extract and decaffeinated. Characterization using the melting point test, phytochemical test, high performance liquid chromatography (HPLC), fourier transform infrared spectroscopy (FTIR) showed that the catechins were isolated. The computational analysis to determine the antioxidant capacity used program named Gaussian 9.0 and Gaussview 5.0 with AM1 semiempirical method for calculation. This study used 10 grams of white tea and produced 2.18 grams of crude catechins and from the decaffeination process obtained 0.109 grams of catechins and 0.053 grams of caffeine from the purification of white tea extracts. Thin layer chromatography (TLC) test was carried out using 4: 1 ethyl acetate: methanol as eluent. From the TLC test results, the catechin samples produced two spots with an Rf value of 0.61 and 0.43 and one spot for the caffeine sample with an Rf value of 0.43. The computational analysis shows that the results are consistent with other studies, namely the highest antioxidant capacity for the compound (-)-epigallocatechin gallate(EGCG) and (-)-epigallocatechin(EGC) has almost the same capacity and tends to be greater than the capacity (-) -epicatechin error (ECG) and (-)-epicatechin (EC). Meanwhile, computational analysis for caffeine compounds shows results to be smaller than the other four major catechin compounds found in Camellia sinensis.